Physiological behaviour of Leucena and Albizia under semi-arid conditions - Filho, José Moacir Pinheiro Lima; Drumond, Marcos Antônio; Maceno, Dilma Silva (Pesquisa Agropecuaria Brasileira, 1992)
A study was conducted to determine Albizia guachepelle (Kuinth) Dug. and Leucaena leucocephala (Lam.) de Wit. physiological responses to guide future planting programs concerning these especies in semi-arid regions. Leaf water potential (Yw), osmotic potencial (Yp), presure potential (YP), stomatal resistence (Re) and transpiration (T) were evaluated during the dry season, two months after a 600 mm rainy period. Leucena decreasing Yw was not followed by reductions on Yp leading YP very close to zero at noon suggesting this species was under stress. The high Re low T between 10:00 a.m. and 2:00 p.m may be considered and effect of this fact. Nevertheless, Albizia adjusted Yp in response to decreasing Yw keeping YP higher and more stable. In addition to that, Re and T values obtained suggest that this species would tolerate more severe soil water and environmental conditions than those observed in this research.